IIUM tracer study 2015 follow up - Rokis, Rohaiza; Wok, Saodah; Zubairi, Ainol Madziah; Dzulkifli, Mariam Adawiah; Md Ghalib, Mohd. Feham; Abdul Rahman, Shukran; Saidin, Aznan Zuhid; Zul Kepli, Mohd Yazid; Tunku Mohd Mokhtar, Tunku Mohar; Wan Husain, Wan Rohaida; Isa, Khadijah; Sulaiman, Muhammad Karimi (Alumni and Global Networking Division, 2016)
The IIUM Tracer Study 2015: Follow Up is the third report of the Tracer Study 2015 project conducted by the International Islamic University Malaysia (IIUM) under the purview of the Alumni and Global Network Division (AGND). This project is a substantial initiative and effort by AGND that receives a strong support from the University to publish a well comprehensive quantitative data report about IIUM’s graduates in collaboration with the Ministry of Higher Education (MOHE). The objective of the survey is to update the employment status of IIUM graduates (Class of 2015). The data was collection 6-months after their graduation (May – October 2016). A total of 4,897 graduates participated in the study, involving 4,186 First Degree graduates and 711 Postgraduate. The respondents for the study were the graduates of the 31st IIUM Convocation. They comprised both undergraduates and Postgraduate from all Kulliyyah. They include the Ahmad Ibrahim Kulliyyah of Laws (AIKOL), Human Science (HS), IIUM Institute of Islamic Banking and Finance (IIIBF), Islamic Revealed Knowledge (IRK), International Institute of Islamic Thought and Civilisation (ISTAC), Kulliyyah of Architecture and Environmental Design (KAED), Kulliyyah of Allied Health Science (KAHS), Kulliyyah of Economics and Management (KENMS), Kulliyyah of Information and Communication Technology (KICT), Kulliyyah of Dentistry (KOD), Kulliyyah of Engineering (KOE), Kulliyyah of Education (KOED), Kulliyyah of Medicine (KOM), Kulliyyah of Nursing (KON), Kulliyyah of Pharmacy (KOP) and Kulliyyah of Science (KOS). Given that the Tracer Study series have yielded important employment related findings and facts that provide useful information to the University in particular and the nation in general, it is hoped that this particular Report will continue to provide useful, comprehensive and exhaustive information to all, particularly to IIUM and MOHE.